1998
DOI: 10.1002/(sici)1098-2744(199809)23:1<36::aid-mc5>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Localization of prostaglandin H synthase isoenzymes in murine epidermal tumors: Suppression of skin tumor promotion by inhibition of prostaglandin H synthase-2

Abstract: The growth factor- and phorbol ester-inducible prostaglandin H synthase (PGHS)-2 has been found to be constitutively overexpressed in epidermal tumors generated by the initiation-promotion protocol in murine skin, whereas the expression of PGHS-1 does not change under these conditions. In this paper we report the intra-tumor distribution of the aberrantly expressed PGHS-2 and the cancer chemopreventive activity of a specific PGHS-2 inhibitor. By immunohistochemical methods using isoenzyme-specific antibodies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
64
0
7

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 27 publications
(37 reference statements)
1
64
0
7
Order By: Relevance
“…Increased expression of this enzyme has been directly associated with many UVB-induced skin inflammatory reactions including edema, erythema, keratinocyte proliferation and epidermal hyperplasia (Rodriguez-Burford et al, 2005). Changes in COX-2 expression have also been linked to the accumulation of DNA damage and mutations, as well as the development of premalignant lesions and skin cancer (Muller-Decker et al, 1998;Fischer et al, 2007). We found that COX-2 mRNA and protein were increased in mouse keratinocytes following UVB exposure.…”
Section: Discussionmentioning
confidence: 72%
“…Increased expression of this enzyme has been directly associated with many UVB-induced skin inflammatory reactions including edema, erythema, keratinocyte proliferation and epidermal hyperplasia (Rodriguez-Burford et al, 2005). Changes in COX-2 expression have also been linked to the accumulation of DNA damage and mutations, as well as the development of premalignant lesions and skin cancer (Muller-Decker et al, 1998;Fischer et al, 2007). We found that COX-2 mRNA and protein were increased in mouse keratinocytes following UVB exposure.…”
Section: Discussionmentioning
confidence: 72%
“…In fact, there is ample evidence that pharmacological (12,15,17) or genetic (44) inactivation of COX-2 may result in a strong inhibition of mouse skin carcinogenesis, pointing to a causal relationship between COX-2 expression and the development of squamous cell carcinomas in skin.…”
Section: Discussionmentioning
confidence: 99%
“…Using the experimental protocol of multistage carcinogenesis in mouse skin (9), we found aberrant COX-2 expression to be associated with the promotion stage (12,15), where initiated keratinocytes harboring a Ha-ras mutation clonally expand into preneoplastic papillomas, some of which subsequently develop into carcinomas. The close interrelation between COX-2 expression and inflammation (16), wounding (7), and skin carcinogenesis (14,15,17) prompted us to analyze the possible consequences of an aberrant overexpression of COX-2 in epidermal tissue in vivo.…”
mentioning
confidence: 99%
See 2 more Smart Citations